2008
DOI: 10.1002/jcb.21663
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid‐induced c‐fos up‐regulation involves cyclic AMP response element‐binding protein activated by mitogen‐ and stress‐activated protein kinase‐1

Abstract: Lysophosphatidic acid (LPA) is a lipid growth factor that exerts diverse biological effects through its cognate receptor-mediated signaling cascades. Recently, we reported that LPA stimulates cAMP response element-binding protein (CREB) through mitogen- and stress-activated protein kinase-1 (MSK1). Previously, LPA has been shown to stimulate c-fos mRNA expression in Rat-2 fibroblast cells via a serum response element binding protein (SRF). However, involvement of CREB in LPA-stimulated c-fos gene expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…SKOV3.ip cells were stimulated with LPA for 20 minutes along with the appropriate vehicle control and the lysates were subjected to the transcription array analysis. Our results indicated that LPA stimulation activated several transcription factors that have previously been shown to be stimulated by LPA including STAT3 [7, 31, 32] and CREB [7, 33, 34], thus establishing the functional validity of our array analysis. In addition, we observed that LPA stimulated the activity of HIF1α by 150-fold compared to the untreated control cells and its activation far exceeded the activation of any other transcription factor on the array (Figure 1A).…”
Section: Resultssupporting
confidence: 71%
“…SKOV3.ip cells were stimulated with LPA for 20 minutes along with the appropriate vehicle control and the lysates were subjected to the transcription array analysis. Our results indicated that LPA stimulation activated several transcription factors that have previously been shown to be stimulated by LPA including STAT3 [7, 31, 32] and CREB [7, 33, 34], thus establishing the functional validity of our array analysis. In addition, we observed that LPA stimulated the activity of HIF1α by 150-fold compared to the untreated control cells and its activation far exceeded the activation of any other transcription factor on the array (Figure 1A).…”
Section: Resultssupporting
confidence: 71%
“…LPA is known for activating different transcription factors, including cFos and STAT3, in different cell lines [ 19 , 20 ], and this was confirmed in MDA-MB-231 and MDA-B02 cells (Figure 5a and 5b ). Because these factors also are regulators of miR-21 expression we evaluated whether cFos and STAT3 could mediate LPA-induced miR-21 expression.…”
Section: Resultsmentioning
confidence: 86%
“…It should be pointed out that while our current study focused on the apoptotic pathways and mechanisms, the LPA effects on cell cycle control and cell proliferation should not be excluded. In fact the PI3K/AKT pathway is known to play an active role in the control of cell cycle [ 35 ]. We found that MEK1 inhibitor (PD98059) significantly inhibited the effect of LPA on the proliferation of Hela cells.…”
Section: Discussionmentioning
confidence: 99%